Stability of Circulating Exosomal miRNAs in Healthy Subjects - David Sanz-Rubio (Nature Portfolio, 2018)
Abstract Exosomes are nano-vesicles present in the circulation that are involved in cell-to-cell communication and regulation of different biological processes. MicroRNAs (miRNAs) are part of their cargo and are potential biomarkers. Methods of exosome isolation and the inter-individual and intra-individual variations in circulating miRNA exosomal cargo have been poorly investigated. This study aims for comparing two exosome isolation methods and to assess the stability of eleven plasma exosomal miRNAs over time. In addition to evaluate miRNA variability of both kits, the effect of freezing plasma before exosome isolation or freezing isolated exosomes on miRNA stability was also evaluated. MiRNA levels were tested in 7 healthy subjects who underwent four different blood extractions obtained in 4 consecutive weeks. One of the isolation kits displayed generally better amplification signals, and miRNAs from exosomes isolated after freezing the plasma had the highest levels. Intra-subject and inter-subject coefficients of variance were lower for the same isolation kit after freezing plasma. Finally, miRNAs that showed an acceptable expression level were stable across the consecutive extractions. This study shows for the first time the stability over time of miRNAs isolated from circulating plasma exosomes, establishing a key step in the use of exosomal miRNAs as biomarkers.